2021
DOI: 10.1186/s43045-021-00142-4
|View full text |Cite
|
Sign up to set email alerts
|

Affective theory of the mind and suicide in women with borderline personality disorder and schizophrenia: a comparative study

Abstract: Background Theory of mind (ToM) is one of the essential components of social cognition. Affective ToM enables us to interpret other’s feelings and behaviors. Borderline personality disorder (BPD) and schizophrenia are two distinct mental disorders, yet they have a mutual deficit in interpreting emotions, thoughts, and intentions which may lead to a higher incidence of suicidality. Studies that involved social cognition, particularly ToM in schizophrenia, or BPD have controversial results. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The 16 studies varied in their objectives. The primary objective of 10 of the studies examined the relationship between some aspect of social cognition and SI or behavior, 40–45 , 50–54 whereas 5 of the studies did not have a primary objective of examining this relationship and reported statistics examining the relationship. 33 , 39 , 46 , 47 , 55 Nine studies included purely cross-sectional analysis of social cognitive variables, 33 , 43–47 , 53–55 5 studies were longitudinal with follow-up intervals ranging from 2 weeks to 20 years, 39–41 , 51 , 52 and 2 studies were cross-sectional case-control designs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 16 studies varied in their objectives. The primary objective of 10 of the studies examined the relationship between some aspect of social cognition and SI or behavior, 40–45 , 50–54 whereas 5 of the studies did not have a primary objective of examining this relationship and reported statistics examining the relationship. 33 , 39 , 46 , 47 , 55 Nine studies included purely cross-sectional analysis of social cognitive variables, 33 , 43–47 , 53–55 5 studies were longitudinal with follow-up intervals ranging from 2 weeks to 20 years, 39–41 , 51 , 52 and 2 studies were cross-sectional case-control designs.…”
Section: Resultsmentioning
confidence: 99%
“… 33 , 39 , 46 , 47 , 55 Nine studies included purely cross-sectional analysis of social cognitive variables, 33 , 43–47 , 53–55 5 studies were longitudinal with follow-up intervals ranging from 2 weeks to 20 years, 39–41 , 51 , 52 and 2 studies were cross-sectional case-control designs. 42 , 50 One included study is a Letter to the Editor that contains empirical data not published elsewhere, but is not a peer-reviewed journal article. 53 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations